2015
DOI: 10.1128/jvi.00802-15
|View full text |Cite
|
Sign up to set email alerts
|

The Baculovirus Antiapoptotic p35 Protein Functions as an Inhibitor of the Host RNA Interference Antiviral Response

Abstract: RNA interference (RNAi) is considered an ancient antiviral defense in diverse organisms, including insects. Virus infections generate double-strand RNAs (dsRNAs) that trigger the RNAi machinery to process dsRNAs into virus-derived short interfering RNAs (vsiRNAs), which target virus genomes, mRNAs, or replication intermediates. Viruses, in turn, have evolved viral suppressors of RNAi (VSRs) to counter host antiviral RNAi. Following recent discoveries that insects mount an RNAi response against DNA viruses, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 53 publications
1
46
0
5
Order By: Relevance
“…However, the expression increased gradually until day 7 postinfection. Suppressors of host RNAi have been reported for other large DNA viruses, for example, iridoviruses and baculoviruses (53,54). The evolutionary conservation of an RNAi suppressor in all ascovirus species implies exposure of ascoviruses to the host RNAi machinery, and probably the dsRNA, the pathway inducer signal, originates from the bidirectional transcription, the main source of dsRNA in the case of DNA viruses (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression increased gradually until day 7 postinfection. Suppressors of host RNAi have been reported for other large DNA viruses, for example, iridoviruses and baculoviruses (53,54). The evolutionary conservation of an RNAi suppressor in all ascovirus species implies exposure of ascoviruses to the host RNAi machinery, and probably the dsRNA, the pathway inducer signal, originates from the bidirectional transcription, the main source of dsRNA in the case of DNA viruses (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Jayachandran et al (16) found abundant 20-nt vsRNAs following infection of Helicoverpa armigera (Lepidoptera; Noctuidae) with the H. armigera single nucleopolyhedrovirus (HaSNPV). In the lepidopteran Sf9 cell line, the predominant size class of baculovirus-derived vsRNAs was also 20 nt in length (39).…”
Section: Discussionmentioning
confidence: 99%
“…During infection in vertebrates, the baculovirus P33 (encoded by AcMNPV orf92 ) is involved in processes such as cell-cycle regulation, apoptosis, differentiations and oncogenic transformations [ 124 ]. P35-mediated inhibition of the evolutionary conserved ICE/ICE-like proteases [ 125 ] results in increased AcMNPV titers and allows successful virus infection in the host [ 126 ]. Neither MdSGHV nor GpSGHV encodes P35 or P49 homologs, which probably underscores the functional and evolutionary differences between SGHVs and baculoviruses.…”
Section: Evolution Of Host’s Apoptosis and Sghvs Escape Strategiesmentioning
confidence: 99%